Call-By-Push-Value A Functional/Imperative Synthesis - Levy, P.B.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2003)
Call-by-push-value is a programming language paradigm that, surprisingly, breaks down the call-by-value and call-by-name paradigms into simple primitives. This monograph, written for graduate students and researchers, exposes the call-by-push-value structure underlying a remarkable range of semantics, including operational semantics, domains, possible worlds, continuations and games.
I Language -- 1. Call-By-Value and Call-By-Name -- 2. Call-By-Push-Value: A Subsuming Paradigm -- 3. Complex Values and Equational Theory -- 4. Recursion and Infinitely Deep CBPV -- II Concrete Semantics -- 5. Simple Models of CBPV -- 6. Possible World Model for Cell Generation -- 7. Jump-With-Argument -- 8. Pointer Games -- III Categorical Semantics -- 9. Semantics in Element Style -- 10. All Models are Categorical Models -- 11. Representing Objects -- IV Conclusions -- 12. Conclusions, Comparisons and Further Work -- Appendices -- Technical Treatment of CBV and CBN -- A.1 The Jumbo ?-Calculus -- A.1.1. Introduction -- A.1.2. Tuple Types -- A.1.3. Function Types -- A.2 Languages and Tranlations -- A.3 Call-By-Value -- A.3.1. Coarse-Grain Call-By-Value -- A.3.2. Fine-Grain Call-By-Value -- A.3.3. From CG-CBV To FG-CBV -- A.4 Call-By-Name -- A.5 The Lazy Paradigm -- A.6 Subsuming FG-CBV and CBN -- A.6.1 From FG-CBV to CBPV -- A.6.2 From CBPV Back to FG-CBV -- A.6.3 From CBN to CBPV -- A.6.4 From CBPV back To CBN -- Models In The Style Of Power-Robinson -- B.1 Intoduction -- B.2 Actions of Monoidal Categories -- B.3 Freyd Categories -- B.4 Judgement Model -- B.5 Enrichment -- B.6 Connectives -- B.7 Modelling CBPV -- B.8 The Full Reflection -- B.9 Theories -- B.10 Conservativity -- References.
Keywords: Programming languages (Electronic computers).; Computer science$1 (BMathematics.s; Category theory (Mathematics).; Homological algebra; Programming Languages, Compilers, Interpreters; Mathematics of Computing; Category Theory, Homological Algebra